On Non-trivially Associated Tensor Categories (European Journal of Pure and Applied Mathematics, 2018)
The purpose of this article is to provide mathematical formulas for some operationson the objects of a non-trivially associated tensor category constructed from a factorization of a group into a subgroup and a set of left coset representatives. A detailed example is provided.